Divine Command, Natural Law, and Redemption in Calvin’s Thought - Jung, Wonho (Theology today, 2020)
Calvin formulates an ethical framework in which the idea of natural law is interwoven with divine command ethics in a way that leads to a new awareness of the unique relationship between God’s authority and human autonomy with regards to morality. For Calvin, God’s creational order is the ultimate source of natural law and the natural moral order perceived by natural reason still provides true sources for human morality. He does not underestimate, however, the noetic effect of sin on natural reason. In fact, Calvin takes seriously the epistemological limitation of the created but fallen natural reason with regard to understanding the true intention of creational moral order in its full scope and meaning. So, he argues that the scriptural revelation does not just complement natural morality, but it redeems it. His view thus successfully rules out extreme views of both natural law and divine command ethics that render morality either utterly autonomous or rigidly heteronomous. For Calvin, God’s authority in morality and the natural moral order are reconciled because the heteronomy of revealed laws and the autonomy of natural law are reintegrated in redeemed reason. In this view, humans can acknowledge the God-commanded biblical moral law by their natural reason because the biblical moral law is a written manifestation of natural law. The regenerate can wholly acknowledge it through the renewal of their natural reason while the unregenerate can partly acknowledge it through common grace of God that preserves functionality of natural reason in fallen humanity to a certain degree.